(untitled) (Journal of Mathematical Study, 2025)
In this paper, we will study the sharp estimates of p-adic weighted Hardy operator on central and noncentral weighted p-adic Morrey spaces. Moreover, we can obtain the sharp bound of generalized p-adic Hardy operator. In addition, the commutator that is generated by the generalized p-adic Hardy operator and the central BMO function is also bounded on p-adic Morrey spaces.